Use of electrogastrography in preclinical studies of cholinergic and anticholinergic agents in experimental pigs - Květina, J; Tachecí, I; Pavlík, M; Kopáčová, M; Rejchrt, S; Douda, T; Kuneš, M; Bureš, J (Physiological research, 2015)
Electrogastrography (EGG) is a non-invasive method for the assessment of gastric myoelectrical activity. Porcine EGG is comparable with human one. The purpose of this study was to evaluate the effect of atropine and neostigmine on the EGG in experimental pigs. Adult female pigs were administrated atropine (1.5 mg i.m., n=6) and neostigmine (0.5 mg i.m., n=6) after the baseline EGG, followed by a 90-min trial recording (MMS, Enschede, the Netherlands). Running spectral analysis was used for the evaluation. The results were expressed as dominant frequency of slow waves and EGG power (areas of amplitudes). Neostigmine increased continuously the dominant frequency and decreased significantly the EGG power. Atropine did not change the dominant frequency significantly. However, atropine increased significantly the EGG power (areas of amplitudes) from basal values to the maximum at the 10-20-min interval. After that period, the areas of amplitudes decreased significantly to the lowest values at the 60-90-min interval. In conclusion, cholinergic and anticholinergic agents affect differently EGG in experimental pigs.
Keywords: Animals; Female; Muscarinic Antagonists; elektrodiagnostika; Atropine; Neostigmine; ženské pohlaví; neostigmin; Time Factors; časové faktory; migrující myoelektrický komplex; prasata; antagonisté muskarinových receptorů; Models, Animal; Electrodiagnosis; žaludek; Swine; zvířata; cholinesterasové inhibitory; atropin; Cholinesterase Inhibitors; Myoelectric Complex, Migrating; Stomach; modely u zvířat